72=6(-2+7x)

Simple and best practice solution for 72=6(-2+7x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=6(-2+7x) equation:


Simplifying
72 = 6(-2 + 7x)
72 = (-2 * 6 + 7x * 6)
72 = (-12 + 42x)

Solving
72 = -12 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
72 + -42x = -12 + 42x + -42x

Combine like terms: 42x + -42x = 0
72 + -42x = -12 + 0
72 + -42x = -12

Add '-72' to each side of the equation.
72 + -72 + -42x = -12 + -72

Combine like terms: 72 + -72 = 0
0 + -42x = -12 + -72
-42x = -12 + -72

Combine like terms: -12 + -72 = -84
-42x = -84

Divide each side by '-42'.
x = 2

Simplifying
x = 2

See similar equations:

| 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 | | 16(1/2x)^4 | | 5(2m+1)=4m+12 | | (1-8/9)/((1/5)/9+2/9) | | 5x^2-10=2x^2 | | -5(y+6)=-10 |

Equations solver categories